The Influence of Transformational Leadership and Compensation on Employee Turnover Intention (Study of Employees of the HR Department of PT Bank Rakyat Indonesia Medan Branch Office) - Pakpahan, Maleakhi; Sihombing, Marlon (PT FORMOSA CENDEKIA GLOBAL, 2024)
Turnover intention refers to an employee's desire to leave the company, and employee turnover in an organization can result in negative impacts. One important aspect in reducing the turnover rate is transformational leadership combined with fair compensation. This research aims to examine the impact of transformational leadership and compensation on turnover intention of HR employees at PT Bank Rakyat Indonesia Medan Branch Office. Using quantitative methods and an associative approach, this research involved a population of 40 employees in the human resources department at PT Bank Rakyat Indonesia Medan Branch Office, with a sample of 38 respondents selected through a purposive sampling technique. Data collection involved questionnaire distribution and literature review. Research findings show that while transformational leadership does not have a significant effect on turnover intention, compensation shows a significant effect.